Fidel castro : my life - Castro, Fidel, 1926-2016.; Ramonet, Ignacio (New York : Scribner, 2014)
Fidel Castro is perhaps the most charismatic and controversial head of state in modern times. A dictatorial pariah to some, he has become a hero and inspiration for many of the world's poor, defiantly charting an independent and revolutionary path for Cuba over nearly half a century. Numerous attempts have been made to get Castro to tell his own story. But only now, in the twilight of his years, has he been prepared to set out the details of his remarkable biography for the world to read. This book is nothing less than his living testament. As he told reporters, his desire to finish checking its text was the one thing that kept him going through his recent illness. He presented a copy of the book in its Spanish edition to his compadre President Hugo ChAvez of Venezuela. In these pages, Castro narrates a compelling chronicle that spans the harshness of his elementary school teachers; the early failures of the revolution; his intense comradeship with Che Guevara and their astonishing, against-all-odds victory over the dictator Batista; the Cuban perspective on the Bay of Pigs and the ensuing missile crisis; the active role of Cuba in African independence movements (especially its large military involvement in fighting apartheid South Africa in Angola); his relations with prominent public figures such as Boris Yeltsin, Pope John Paul II, and Saddam Hussein; and his dealings with no less than ten successive American presidents, from Eisenhower to George W. Bush. Castro talks proudly of increasing life expectancy in Cuba (now longer than in the United States); of the half million students in Cuban universities; and of the training of seventy thousand Cuban doctors nearly half of whom work abroad, assisting the poor in Africa, Asia, and Latin America. He is confronted with a number of thorny issues, including democracy and human rights, discrimination toward homosexuals, and the continuing presence of the death penalty on Cuban statute books. Along the way he shares intimacies about more personal matters: the benevolent strictness of his father, his successful attempt to give up cigars, his love of Ernest Hemingway's novels, and his calculation that by not shaving he saves up to ten working days each year. Drawing on more than one hundred hours of interviews with Ignacio Ramonet, a knowledgeable and trusted interlocutor, this spoken autobiography will stand as the definitive record of an extraordinary life lived in turbulent times.
Title from resource description page (Recorded Books, viewed October 13, 2014).
Notes and Index
Keywords: Castro, Fidel, -- 1926-2016 -- Interviews; Castro, Fidel, -- 1926-2016; Since 1933; Heads of state -- Cuba -- Interviews; Heads of state -- Cuba -- Biography; Chefs d'Etat -- Cuba -- Entretiens; Chefs d'Etat -- Cuba -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Personal Memoirs; Heads of state; Cuba -- History -- 1959-1990.; Cuba -- History -- 1990-; Cuba -- History -- 1933-1959.; Cuba -- Histoire -- 1959-1990.; Cuba -- Histoire -- 1990-; Cuba -- Histoire -- 1933-1959.; Cuba; Biographies; History; Interviews